HEPATOPROTECTIVE EFFECT OF CRYOPRESERVED PLACENTA EXTRACT ON THE TETRACHLOROMETHANE LIVER INJURY - Illia Koshurba (Eastern Ukrainian Medical Journal, 2022)
Introduction. Toxic lesions of the hepatobiliary system are an important medical and social problem due to the steady increase in the frequency of chemical hepatosis, which develops as a result of accumulation of various xenobiotics in the body. Tetrachloromethane (CCl4) is one of the most studied hepatotoxins. Biochemical and pathomorphological changes in the liver lesions modeled by the administration of CCl4 are analogous to acute hepatitis of various etiologies in humans. As a potential hepatoprotective agent, cryopreserved placenta extract (CPE) attracted our attention. The objective is to characterize the effect of cryopreserved placenta extract on the functional state of the liver of rats with tetrachloromethane-induced damage. Materials and Methods. In vivo study was conducted on 28 male rats weighing 200–220 g. Acute CCl4-induced hepatitis was reproduced by injecting a 50.0% oil solution of CCl4 at a dose of 10 ml/kg body weight of the animal once, which caused acute fatty liver dystrophy. Animals were sacrificed 24 hours after the administration of CCl4. CPE was administered once per day for five days before CCl4 administration. The research material was blood and liver homogenates. The concentration of bilirubin in blood was determined by the spectrophotometrical method. The content of adenosine monophosphoric, adenosine diphosphoric, and adenosine triphosphoric acids was studied in the deproteinized homogenate by chromatographic method. Results and discussion. It was established that the development of CCl4-induced hepatitis is accompanied by the formation of a cholestatic syndrome and a disorder of energy metabolism in liver tissues. This was indicated by an increase (p < 0.001) in the level of total bilirubin by 4.7 times and a decrease (p < 0.001) in the energy charge by 42.6% compared to the indicators of intact rats. Prophylactic five-day administration of CPE led to a decrease (p < 0.001) in the level of total bilirubin by 32.1% and a decrease (p < 0.001) in the levels of direct and indirect bilirubin by 10.6% and 65.1%, respectively, compared to the indicators of animals with experimental toxic hepatitis. This indicated the weakening of the cholestatic syndrome and, indirectly, the weakening of inflammatory infiltration against the background of cytolytic processes in the liver. CPE had an energy-stabilizing effect on hepatocytes of rats with simulated tetrachloromethane liver injury. This was indicated by an increase (p = 0.02) of the energy charge by 18.2% compared to the indicators in the control group. Conclusions. The study showed anticholestatic and energy-stabilizing activity of the cryoextract of placenta used as a prophylactic measure in the model of tetrachloromethane-induced hepatitis.